An increase in new Sargassum (Phaeophyceae) blooms along the coast of the East China Sea and Yellow Sea. Issue 4 (4th July 2019) - Zhang, Jianheng; Ding, Xiaowei; Zhuang, Minmin; Wang, Shiying; Chen, Li; Shen, Hui; He, Peimin
ABSTRACT: New macroalgal blooms caused by the genus Sargassum have been occurring along the coast of China. In particular, in 2017, Sargassum blooms covered up to 188 km 2 and drifted into the offshore region of Jiangsu Province, the traditional area for Pyropia aquaculture. This resulted in an enormous loss of production of Pyropia . This study was designed to identify the species composition, phylogenetic relationships, and possible origin of the free-floating Sargassum populations in the Yellow Sea and East China Sea. Results from morphological observations and molecular identification showed that Sargassum horneri was the only species comprising the blooms. Based on further satellite remote sensing analysis, the suspected origin of the blooms was the coastal area of Zhejiang Province, where S. horneri is widely distributed. This study increases our understanding of the importance of controlling the spread of macroalgae blooms.